Studi Etnografi Tentang Perencanaan Keuangan pada Kelompok Sosial Masyarakat Muslim Kota Batu - S, Basir; Rozi, Choirul (Fakultas Ekonomi, UIN Maliki Malang, 2020)
One of the financial successes can be achieved through family financial planning. The purpose of this study is to see how the views of the priyayi Muslim community groups on property. The results of the study show that the views of the household on the priyayi Muslim family in the city of Batu concerning the property are something that is entrusted by Allah SWT. The process of earning an income is that he will strive to make a halal income in terms of the essence, the way to obtain it, and the aspects of His utilization how to determine the priority scale of needs, which is based on the principle of demand and establish themselves from the concept of tabzir or spree on various kinds of needs that they need during their lives. The way to do financial planning is based on a budget management system that applies the concept of Falah in every financial allocation, which is not only focused on the world but also based on the hereafter as well